Promosi Kesehatan melalui Media Audiovisual dan Leaflet dalam Mendorong Perilaku IVA Test pada Wanita Usia Subur - Sulistyo Dewi Wahyu Rini; Vira Amelia; Nanang Muhibbuddin (Universitas Baiturrahim, 2026)
Background: The low coverage of VIA screening indicates that awareness among women of reproductive age regarding the importance of early detection of cervical cancer still needs to be improved. This condition highlights the need for more effective and acceptable health promotion strategies, particularly through the use of educational media that are appropriate to the characteristics of the target population. Objective: This community service activity aimed to improve VIA screening behavior among women of reproductive age through health promotion using leaflet and audiovisual media, as well as to compare the outcomes of both media. Methods: The activity was conducted in the form of health promotion for women of reproductive age who were divided into two groups, namely a leaflet group and an audiovisual group. A total of 100 women of reproductive age who met the target criteria participated in this activity. Behavioral evaluation was carried out through observation of participants’ participation in undergoing VIA screening at health service facilities. An evaluative analysis was performed to assess differences in the outcomes of health promotion between the two groups. Results: The evaluation results showed that in the group receiving health promotion using leaflet media, 28% of participants underwent VIA screening, while 72% did not. In contrast, in the group receiving health promotion using audiovisual media, 64% of participants underwent VIA screening and 36% did not. Comparative analysis indicated a meaningful difference between the use of leaflet and audiovisual media in encouraging VIA screening behavior. Conclusion: Health promotion using audiovisual and leaflet media demonstrated differences in effectiveness in encouraging VIA screening behavior among women of reproductive age. Audiovisual media provided a more interactive learning experience, while leaflets helped strengthen understanding through repeated reading